Challenges to establish the diagnosis of aspergillosis in non-laboratory animals: looking for alternatives in veterinary medicine and demonstration of feasibility through two concrete examples in penguins and dolphins - Desoubeaux, Guillaume; Cray, Carolyn; Chesnay, Adélaïde (Frontiers in Cellular and Infection Microbiology, 2022)
Aspergillosis remains tough to diagnose in animals. Laboratory kits are far less developed than for human medicine, and only few studies were actually carried out to validate their utility in routine. To circumvent the current limitations, veterinarians and scientific staff have to propose alternative methods. Extrapolating from human diagnostic tools and using innovative technology can meet their expectations. In the present overview, two concrete examples were addressed to illustrate how challenging can be the processes to complete the diagnosis of aspergillosis in penguins and dolphins. Specific focus will be made on the smart application of simple testing in blood based on serological assay or protein electrophoresis, and on the possibilities offered by metabolomics / proteomics to discover potential new biomarkers. In conclusion, one should stay aware that the diagnostic approach of aspergillosis in veterinarian medicine cannot be totally copied from the practices in human medicine, but nonetheless has been frequently inspired from.